Effects of Mesona chinensis polysaccharide on the thermostability, gelling properties, and molecular forces of whey protein isolate gels. (15th August 2020) - Jiang, Lian; Ren, Yanming; Xiao, Yuehuan; Liu, Shanshan; Zhang, Jiahui; Yu, Qiang; Chen, Yi; Xie, Jianhua
Highlights: The physicochemical properties of Mesona chinensis polysaccharide were detected. MCP had significant effect on the gel properties of MCP-WPI mixed gels. Creep/recovery rate and elasticity increased with MCP addition. Disulfide, hydrophobic, and hydrogen bond interactions play a major role in gels. Abstract: The effects of Mesona chinensis polysaccharide (MCP) on the water holding capacity (WHC), thermostability, rheological properties, microstructure, and molecular forces of MCP-whey protein isolate (WPI) gels were investigated. Results showed that the MCP-WPI gels had higher WHC, thermal stability, and thermal transition temperature than the WPI gel. The apparent viscosities, loss modulus ( G″ ), and storage modulus ( G' ) of the MCP-WPI gels were increased with the MCP concentration. Creep recovery experiment showed that the recovery rate increased with the MCP increased, and MCP-WPI gels had good elasticity and rigid structure. Texture profile analysis (TPA) results showed that gel strength and rupture stress were increased with the MCP addition. Scanning electron microscope (SEM) showed that dense water cavity was formed when the MCP concentration reached 2.0 %. The main molecular forces of the gels were disulfide, hydrophobic, and hydrogen bonding interaction. MCP played a critical role in the formation of MCP-WPI gels.